Extensive Tracking of Nomadic Waterbird Movements Reveals an Inland Flyway - Heather M. McGinness; Micha V. Jackson; Luke Lloyd‐Jones; Freya Robinson; Art Langston; Louis G. O'Neill; Shoshana Rapley; Melissa Piper; Micah Davies; Jessica Hodgson; John M. Martin; Richard Kingsford; et al. (Ecology and Evolution)
ABSTRACT Waterbirds are highly mobile and have the ability to respond to environmental conditions opportunistically at multiple scales. Mobility is particularly crucial for aggregate‐nesting species dependent on breeding habitat in arid and semi‐arid wetlands, which can be ephemeral and unpredictable. We aimed to address knowledge gaps about movement routes for aggregate‐nesting nomadic waterbird species by tracking them in numbers sufficient to make robust assessment of their movement patterns. We hypothesised that analysis of long‐distance movements would identify common routes with consistent environmental features that would be useful as context for conservation management. We used GPS satellite telemetry to track the movements of 73 straw‐necked ibis (Threskiornis spinicollis) and 42 royal spoonbills (Platalea regia) over 7 years (2016‐2023). We used these data to identify long‐distance movements and to demarcate and characterise movement routes. We identified common routes used by both species, including a ‘flyway’ over 2000 km long, spanning Australia's Murray–Darling Basin from the south‐west to the north‐east. This flyway connects important breeding sites and is characterised by flat, open/unforested areas with low elevations of < 350 m and mid to high rainfall. The flyway corresponds to an area west of Australia's Great Dividing Range, which appears to act as a low‐permeability barrier to the movement of both species. Identification of an inland flyway for waterbirds in Australia provides important context for multi‐jurisdictional cooperation and strategic management. Where resources are limited, water and wetland management efforts (e.g., environmental watering) should be preferentially located within this route. Similarly, targeting threat mitigation within common movement routes may have disproportionate importance for long‐term population viability. Given the widespread distribution of similar species globally, there are likely to be other flyways worthy of scientific and conservation management attention that could be identified using our approach.